Pendidikan Multikultural di Sekolah - Ahmad; Anis Binti Roysatul Mahmudah (Indonesian Journal of Humanities and Social Sciences, 2022)
Indonesia is a country that has a variety of cultures, customs, races, ethnicities, religions, and many more. For this reason, Indonesian society is considered very plural. Diverse cultures with various characteristics and characters became a problem due to a lack of understanding of diversity. Friction regarding race, religion, ethnicity, customs, and culture continues to occur due to the weak cultural awareness of the community. Education can form an attitude of tolerance, mutual respect, and mutual respect. Establishing and developing multicultural education in schools can be the right area to become a vehicle for learning multicultural education in schools for students or educators. Multicultural education is essential so students will be ready and aware to become members of a plural society.